The role of police in primary investigation of terrorism cases in Jordan - Al-Hawari, Saed Zayed Mohammad; Ansari, Abdul Haseeb (Inderscience Publishers, 2012)
This paper examines the role of law by enforcement agents, especially the police, in investigating the crime of terrorism in Jordan, and focuses on the procedural rules for the investigation of terrorism, the nature of the police agencies in the Jordanian criminal justice system, the main traditional and specified, investigatory and accusatory authority of police agents and the basic right of protection of the accused against actions taken by government agencies, at the preliminary investigation stage. In this article, the authors have adopted the qualitative research methodology. The paper concludes that in order to provide more realistic protection to the accused during investigation, the law should be reviewed.